USING ACRONYM STRATEGIES TO TEACH ENGLISH TENSES: A CASE STUDY OF NON-ENGLISH-SPEAKING BACKGROUND STUDENTS - Mukhzamilah; Mintowati, Maria; Mulyono; Putra, Octa Pratama; Khushik, Ghulam Abbas (Widya Mandala Surabaya Catholic University, 2026)
The mastery of English tenses remains a significant challenge for many EFL learners, often exacerbated by traditional, abstract pedagogical methods that contribute to cognitive overload and performance anxiety. This study investigates the efficacy of food-based mnemonic acronyms as a cognitive scaffold to facilitate the learning and retention of grammatical structures. Adopting a qualitative research design, the study employs thematic analysis to examine the cognitive and affective shifts in the learning processes of four university students—BAW, PRN, JMM, and SDK—selected based on their diverse academic backgrounds and challenges with tense acquisition. The thematic analysis reveals that these associative tools function as vital